Novel CPVT-Associated Calmodulin Mutation in CALM3 (CALM3-A103V) Activates Arrhythmogenic Ca Waves and Sparks. (August 2016) - Gomez-Hurtado, Nieves; Boczek, Nicole J.; Kryshtal, Dmytro O.; Johnson, Christopher N.; Sun, Jennifer; Nitu, Florentin R.; Cornea, Razvan L.; Chazin, Walter J.; Calvert, Melissa L.; Tester, David J.; Ackerman, Michael J.; Knollmann, Björn C.
Abstract : Background—: Calmodulin (CaM) mutations are associated with severe forms of long QT syndrome and catecholaminergic polymorphic ventricular tachycardia (CPVT). CaM mutations are found in 13% of genotype-negative long QT syndrome patients, but the prevalence of CaM mutations in genotype-negative CPVT patients is unknown. Here, we identify and characterize CaM mutations in 12 patients with genotype-negative but clinically diagnosed CPVT. Methods and Results—: We performed mutational analysis of CALM1, CALM2, and CALM3 gene-coding regions, in vitro measurement of CaM-Ca 2+ (Ca)-binding affinity, ryanodine receptor 2–CaM binding, Ca handling, L-type Ca current, and action potential duration. We identified a novel CaM mutation—A103V—in CALM3 in 1 of 12 patients (8%), a female who experienced episodes of exertion-induced syncope since age 10, had normal QT interval, and displayed ventricular ectopy during stress testing consistent with CPVT. A103V modestly lowered CaM Ca-binding affinity (3-fold reduction versus WT-CaM), but did not alter CaM binding to ryanodine receptor 2. In permeabilized cardiomyocytes, A103V-CaM (100 nmol/L) promoted spontaneous Ca wave and spark activity, a cellular phenotype of ryanodine receptor 2 activation. Even a 1:3 mixture of A103V-CaM:WT-CaM activated Ca waves, demonstrating functional dominance. Compared with long QT syndrome D96V-CaM, A103V-CaM had significantly less effects on L-type Ca current inactivation, did not alter action potential duration, and caused delayed afterdepolarizations and triggered beats in intact cardiomyocytes. Conclusions—: We discovered a novel CPVT mutation in the CALM3 gene that shares functional characteristics with established CPVT-associated mutations in CALM1 . A small proportion of A103V-CaM is sufficient to evoke arrhythmogenic Ca disturbances via ryanodine receptor 2 dysregulation, which explains the autosomal dominant inheritance. Abstract : Supplemental Digital Content is available in the text.